Otoritas Estetik pada Pertunjukan Tari Dolalak di Kabupaten Purworejo, Jawa Tengah - Nanik Sri Prihatini (PANGGUNG, 2023)
The Dolalak dance in Purworejo Regency is interesting to observe because it has developed with a creative appearance. At first Dolalak was presented by male dancers who seemed dashing, but with the presence of female dancers Dolalak appeared coquettish or cool. This happens because of the aesthetic authority exercised by the artists, both the composing artists and the performers. The purpose of this study was to identify and analyze the authority associated with the aesthetic touch performed by a dance leader and choreographer for the Dolalak dance, namely Melania Sinaring Putri. This research is a qualitative research used to look at the cultural phenomena of the Dolalak dance performance with a social approach that uses the theory of authority, the theory of work on, and the theory of dance creation. Data collection was carried out by way of literature study and interviews. The results of this study can be concluded that Dolalak is currently experiencing quite encouraging developments because of the creative touch of the artists as the owners. Keywords: Dolalak, authority, aesthetics, and work on.